The Effect of Communication, Motivation and Teamwork on Employee Work Effectiveness Through Job Satisfaction as a Mediation Variable (Study at the Sub-district Office Near Lamongan Regency) - Arif Bakhtiar; Muhamad Imam Syairozi; Abid Muhtarom; Sutinem, Sutinem (Jurnal Multidisiplin Sahombu, 2025)
Generally in an agency or organization, whether it is a government or private organization, a role in the form of employee performance is needed, because employees are very decisive in achieving or not the organization or government agency. The purpose of this study is Communication, Motivation and Teamwork on Employee Work Effectiveness Through Job Satisfaction as a Mediating Variable, this study uses a quantitative method, using 100 respondents and using the Pls-Sem 3 analysis tool. The results of this study are that job satisfaction mediates the relationship between motivation and work effectiveness, conversely job satisfaction does not mediate the relationship between communication and teamwork on work effectiveness.